2014
DOI: 10.1136/bmj.g7346
|View full text |Cite
|
Sign up to set email alerts
|

Televised medical talk shows--what they recommend and the evidence to support their recommendations: a prospective observational study

Abstract: Objective To determine the quality of health recommendations and claims made on popular medical talk shows.Design Prospective observational study. Setting Mainstream television media. SourcesInternationally syndicated medical television talk shows that air daily (The Dr Oz Show and The Doctors). Interventions Investigators randomly selected 40 episodes of each ofThe Dr Oz Show and The Doctors from early 2013 and identified and evaluated all recommendations made on each program. A group of experienced evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 11 publications
0
56
0
1
Order By: Relevance
“…Given the current obesity crisis Ogden Carroll, Lawman, Fryar, Kruszon-Moran, Kit, & Flegal, 2016), it has become increasing clear that certain environmental constraints raise the risks for obesity (Myers, Slack, Martin, Broyles, & Heymsfield, 2016), and that there is a remarkable amount of nutritional misinformation circulating in popular culture (Korownyk, Kolber, McCormack, Lam, Overbo, Cotton, & Allan, 2014;Wansink, 2005). Nutritional knowledge has thus become essential for maintaining a healthy lifestyle.…”
Section: Post-secondary Nutrition Science Educationmentioning
confidence: 99%
“…Given the current obesity crisis Ogden Carroll, Lawman, Fryar, Kruszon-Moran, Kit, & Flegal, 2016), it has become increasing clear that certain environmental constraints raise the risks for obesity (Myers, Slack, Martin, Broyles, & Heymsfield, 2016), and that there is a remarkable amount of nutritional misinformation circulating in popular culture (Korownyk, Kolber, McCormack, Lam, Overbo, Cotton, & Allan, 2014;Wansink, 2005). Nutritional knowledge has thus become essential for maintaining a healthy lifestyle.…”
Section: Post-secondary Nutrition Science Educationmentioning
confidence: 99%
“…It's common for Dr. Oz to offer some plausible mechanism from test tube experiments conducted by manufacturers, combined with personal anecdotes from his own or consumers' experience, to support the products he's promoting. A study of 80 recommendations made on The Dr. Oz Show in early 2013 found that published evidence supported 46 percent of recommendations, contradicted 15 percent, and did not support 39 percent [20]. Yet, his visible display of inconclusive evidence merely highlights questions about the boundaries of what counts as legitimate evidence in modern medicine.…”
Section: Dr Oz and The Problems Of Self-regulationmentioning
confidence: 99%
“…Television is well established to be an important source of health information for members of the general public 13. We have found that CPR on televised medical dramas is inadequately performed.…”
Section: Discussionmentioning
confidence: 99%